PEMIKIRAN KEBIJAKAN FISKAL EKONOMI ISLAM - M.Si, Gampito (JURIS (Jurnal Ilmiah Syariah), 2010)
By integrating zakat (divine tax) into fiscal policy, the government can decide fiscal which are mutually beneficial for both  Moslem and government. This integration will in turn affect traditional law of zakat. Furthermore, the influence of modern fiscal policies toward zakat cover the subject, object, tariff and distribution of zakat. The subject of zakat in this fiscal policies include enterprise and individuals as well. The object of zakat in this term includes not only those mentioned by the prophet but also any kinds of wealth as defined by the government.